The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.1177/1528083720980172
|View full text |Cite
|
Sign up to set email alerts
|

The friction and wear behaviors of self-lubricating composites with two types of warp-knitted fabric structures

Abstract: Replacing the traditional self-lubricating fabric composites with new type of wear-resistant composite reinforced by warp-knitted fabrics PTFE-Nomex and PTFE-Nomex/Nomex (self-lubricating fiber: PTFE, reinforcing fiber: Nomex), in which the hybrid graphite/graphene particle modified phenolic is used as the adhesive resin. The influence of the fabric structure on the friction and wear properties of self-lubricating fabric composites was evaluated by the ball-on-disk and bearing friction tests. And the wear mech… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 21 publications
0
7
0
Order By: Relevance
“…A hybrid poly­(tetrafluoroethylene) (PTFE)/Nomex fabric laminate composite is a material with excellent tribological and mechanical properties that can be used in water-lubricated bearings of ships because the PTFE fiber has enhanced self-lubricating effects to ensure good tribological properties. Nomex fiber has a large binding force with an adhesive resin to ensure good mechanical properties. Excellent underwater wear and water resistance as well as high underwater strength are required for water-lubricated bearing liner materials, which are closely related to the adhesive resin. , …”
Section: Introductionmentioning
confidence: 99%
“…A hybrid poly­(tetrafluoroethylene) (PTFE)/Nomex fabric laminate composite is a material with excellent tribological and mechanical properties that can be used in water-lubricated bearings of ships because the PTFE fiber has enhanced self-lubricating effects to ensure good tribological properties. Nomex fiber has a large binding force with an adhesive resin to ensure good mechanical properties. Excellent underwater wear and water resistance as well as high underwater strength are required for water-lubricated bearing liner materials, which are closely related to the adhesive resin. , …”
Section: Introductionmentioning
confidence: 99%
“…14 The study of composition and structure of fabric on the friction and wear properties of self-lubricating fabric composites is very important for the development of composites and their applications in self-lubricating joint bearings. It is found that the weaving mode, 15,16 weaving density, 17 warp and weft density 18,19 and yarn type of fabric can affect the resin wettability, interfacial adhesion and bearing capacity, [20][21][22] and then significantly affect the mechanical properties and tribological properties of the self-lubricating fabric composites. Li et al woven copper yarns into Nomex/PTFE fabric to improve the strength of the yarns and fabric, so that the self-lubricating fabric lining composite showed better wear resistance.…”
Section: Introductionmentioning
confidence: 99%
“…Cui et al discussed the tribological mechanism of the self-lubricating material, and pointed that the Nomex/PTFE fabric could form stable transfer film on the spherical plain bearing under low temperature [14]. Yu et al carried out the ball-ondisk and bearing tribological tests to study the friction and wear behavior of the PTFE-Nomex and the PTFE-Nomex/Nomex composites [15]. He obtained that the tribological behaviors of two kind composite were different with increasing sliding distance.…”
Section: Introductionmentioning
confidence: 99%